Using Podcast Media on Teaching Listening in New Normal Era - Nenna Firmi Fatika; Endang Mastuti Rahayu (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2021)
The objective of this study was to describe the application of using podcast media on the teaching listening. The students did not interest and experience difficulty while learning listening because the media of listening was too monotonous and lack of innovation. Podcast is a combination of two words namely